Minimum lymph node yield in elective level I–III neck dissection. (8th March 2017) - Pou, Jason D.; Barton, Blair M.; Lawlor, Claire M.; Frederick, Christopher H.; Moore, Brian A.; Hasney, Christian P.
Abstract : Objectives/Hypothesis: Unlike lymphadenectomy at other sites, there is no discrete lymph node count defining an adequate neck dissection. The purpose of this study was to determine the minimum lymph node yield (LNY) of an elective level I–III neck dissection required to reliably capture any positive nodes present in these nodal basins. Study Design: Retrospective single‐institution analysis. Methods: All patients with the diagnosis of head and neck squamous cell carcinoma who underwent elective level I–III neck dissection between 2004 and 2015 at our institution were analyzed. Preoperatively, patients had no clinical or radiographic evidence of lymphadenopathy. Patients with unknown number of lymph nodes on pathology report were excluded. Age, gender, race, history of radiation, tumor subsite, stage, surgeon, LNY, and number of positive nodes were recorded; bilateral neck dissections were reported separately. Results: One hundred eighteen level I–III neck dissections met criteria and were included in the study. Mean LNY was 21.15, and metastatic disease was present in 24.5% of cases, with 8.4% of cases being N2. The highest portion of positive lymph nodes was present in the group with 18 to 24 lymph nodes (36%), which was significantly higher than the group with <18 (14.89%) ( P = .044). Conclusions: Although there is no accepted minimum for LNY in level I–III neck dissection, at least 18 nodes may be considered an adequate LNY. Such a yield reliably allows for capture of occult disease within these nodal basins. Level of Evidence: 4. Laryngoscope, 127:2070–2073, 2017